User Experience Design Practices in Industry (Case Study from Indonesian Information Technology Companies) - Isnan Nugraha; Agung Fatwanto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2021)
User Experience (UX) is a term that has received a lot of attention in the last decade. The number of industries whose consider the importance of implementing the UX design process within their development cycle has increased. Therefore, we think it is important to investigate how UX design processes are implemented in the industries. In this research, we take a qualitative approach with descriptive methods by investigating six information technology companies in Indonesia. As a result, we found that most of these information technology companies implement the UX design process as part of their operation and consider that the UX design process is an important part of software development. Each company has its order and priorities in regard to the UX design processes and only follows their established UX design process framework in order to meet their product development requirements. We also found that there are different UX design process approaches from these six companies.